Re-validation of Otocinclus arnoldi Regan and reappraisal of Otocinclus phylogeny (Siluriformes: Loricariidae) - Lehmann A,Pablo (2010)
Otocinclus arnoldi from the La Plata basin is resurrected from the synonymy of O. flexilis described from the rio Jacuí drainage, based on three distinguishing features: the possession of five branched pectoral-fin rays, the larger number of enlarged odontodes on the tip of the parieto-supraoccipital posterior process, and having the prootic involved in the contact with the hyomandibular articular condyle. These species are also compared to O. mimulus, a third species described from the Paraná River basin, and the three species are rediagnosed. A reassessment of the phylogenetic relationships of all species of Otocinclus shows a well-supported clade composed of (O. xakriaba ((O. mimulus, O. arnoldi) (O. affinis, O. flexilis))) from the eastern-draining river basins of the Brazilian Shield as sister-group to a clade including all remaining Otocinclus species which are distributed on a wide lowland area of the Amazonas, Paraguay, and Orinoco basins.